Impairment of NKG2D-Mediated Tumor Immunity by TGF-β - Lazarova, Mariya; Steinle, Alexander (Frontiers in Immunology, 2019)
Transforming growth factor-β (TGF-β) suppresses innate and adaptive immune responses via multiple mechanisms. TGF-β also importantly contributes to the formation of an immunosuppressive tumor microenvironment thereby promoting tumor growth. Amongst others, TGF-β impairs tumor recognition by cytotoxic lymphocytes via NKG2D. NKG2D is a homodimeric C-type lectin-like receptor expressed on virtually all human NK cells and cytotoxic T cells, and stimulates their effector functions upon engagement by NKG2D ligands (NKG2DL). While NKG2DL are mostly absent from healthy cells, their expression is induced by cellular stress and malignant transformation, and, accordingly, frequently detected on various tumor cells. Hence, the NKG2D axis is thought to play a decisive role in cancer immunosurveillance and, obviously, often is compromised in clinically apparent tumors. There is mounting evidence that TGF-β, produced by tumor cells and immune cells in the tumor microenvironment, plays a key role in blunting the NKG2D-mediated tumor surveillance. Here, we review the current knowledge on the impairment of NKG2D-mediated cancer immunity through TGF β and discuss therapeutic approaches aiming at counteracting this major immune escape pathway. By reducing tumor-associated expression of NKG2DL and blinding cytotoxic lymphocytes through down-regulation of NKG2D, TGF-β is acting upon both sides of the NKG2D axis severely compromising NKG2D-mediated tumor rejection. Consequently, novel therapies targeting the TGF-β pathway are expected to reinvigorate NKG2D-mediated tumor elimination and thereby to improve the survival of cancer patients.